1989
DOI: 10.1177/028418518903000206
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the Pettersson Scoring System

Abstract: By means of the Pettersson scoring system, the degree of severity of haemophilic arthropathy in 128 knee, elbow and ankle joints was estimated by 5 radiologists. Their scores varied on average by approximately 3 points. Minimal and maximal joint involvement were scored consistently; exclusion of haemophilic arthropathy was possible with the highest degree of certainty. With regard to changes of a moderate degree agreement was seldom reached. With precisely defined characteristics, a high degree of consistency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…Results of previous reliability studies showed that radiographic scoring systems for evaluation of haemophilic arthropathy are slightly more reliable for assessment of ankles compared with knees [3], which is the opposite of the results of this study. Although different imaging modalities have been used in the study that evaluated radiographic scoring systems and the current study we hypothesized that differences in the degree of severity of findings may have played a role on the reliability of the scoring systems according to the joint under evaluation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results of previous reliability studies showed that radiographic scoring systems for evaluation of haemophilic arthropathy are slightly more reliable for assessment of ankles compared with knees [3], which is the opposite of the results of this study. Although different imaging modalities have been used in the study that evaluated radiographic scoring systems and the current study we hypothesized that differences in the degree of severity of findings may have played a role on the reliability of the scoring systems according to the joint under evaluation.…”
Section: Discussioncontrasting
confidence: 99%
“…Arthropathy is a major cause of morbidity for boys with severe haemophilia, especially for those who are not on a prophylactic scheme [1]. Haemarthrosis may occur in one or several joints and may progress to a destructive, disabling arthropathy [2] that most commonly affects large joints such as knees and ankles [3]. Once radiographic changes are present the clinical course of the arthropathy is usually progressive and irreversible.…”
Section: Introductionmentioning
confidence: 99%
“…These have been widely used in practice and in clinical studies. However, the clinical score has never been validated and the radiological score, although validated, lacks sensitivity and clinical correlation (Erlemann et al, 1987). Limitations with regard to inter-observer variability, ambiguity in definition and lack of clinical significance of certain parameters included in the scores have been noted (Hamel et al, 1988).…”
Section: Dose and Response -Difficulties In Haemophiliamentioning
confidence: 99%
“…These scores have been recommended by the World Federation of Haemophilia (WFH); both have been widely used [6][7][8] but have considerable limitations. The Pettersson score is a validated score [9,10], but it assesses osteochondral changes only and is therefore not suitable to detect early joint damage occurring in soft tissues [11]. The clinical score is a physical examination score which has never been validated and is consistently lower than the Pettersson score [8,12].…”
Section: Introductionmentioning
confidence: 99%